Taiwanese Consumers’ Perceptions of Local and Global Brands: An Investigation in Taiwan Computer Industry - Hsieh, Ya-Yun (2010)
This study aims to investigate how consumers in a newly developed country, Taiwan, perceive local brands and global brands in the computer industry. To access an in-depth understanding and evaluate factors that influence consumers’ assessment of local and global brands, the country-of-origin effect and the association of brand origin are investigated; the effect of consumer ethnocentrism is addressed; and the cultural aspects on collectivism and face concept are examined.